2022
DOI: 10.4018/ijmbl.297976
|View full text |Cite
|
Sign up to set email alerts
|

Online Collaborative Learning Using Microsoft Teams in Higher Education Amid COVID-19

Abstract: Due to the Covid-19 pandemic, most universities needed to move to online teaching and learning, in some cases with very limited knowledge or experience in running online programmes. Engaging students online has become an imminent challenge that universities and academics are still trying to address. This paper reports on the findings from the experience of making the transition from an established collaborative learning activity delivered in a face-to-face environment to online collaborative learning supported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Teachers' responses show different opinions about online classrooms being a perfect environment for developing practical speaking abilities and think that technical problems associated with online teaching waste time. However, online classes decrease students' anxiety and affect fluency because using technology in online classes, helps students deliver speaking tasks better; This is in agreement with Tan et al (2022), Albaqami and Alzahrani (2022), and Truong and Murray (2019) who showed how online tools have a positive effect on students' motivation and agrees with statement 15.…”
Section: Resultssupporting
confidence: 78%
“…Teachers' responses show different opinions about online classrooms being a perfect environment for developing practical speaking abilities and think that technical problems associated with online teaching waste time. However, online classes decrease students' anxiety and affect fluency because using technology in online classes, helps students deliver speaking tasks better; This is in agreement with Tan et al (2022), Albaqami and Alzahrani (2022), and Truong and Murray (2019) who showed how online tools have a positive effect on students' motivation and agrees with statement 15.…”
Section: Resultssupporting
confidence: 78%
“…Preparing teaching and learning processes enhancing students' metacognition aided by IoT facilitation is one of the solutions for learning preparation generation in the 4.0. revolution and 5.0 society. Microsoft Teams (MS Teams) is a workspace platform Microsoft Corp. provides for real-time collaboration and communication (Tan et al, 2022;Deželak et al, 2023;Ma & Buechler, 2021). Many available features are applicable for online learning and metacognitive enhancement.…”
Section: Online Learning Using Website Hyperlink In the Ms Platform E...mentioning
confidence: 99%
“…Here in this paper, we employed discovery learning model with a website hyperlinks facilities involvement in the Microsoft Teams platform to facilitate learning biological coordination system and examined the effectiveness of such an online platform in enhancing metacognition in terms of metacognitive knowledge and awareness. Microsoft Teams, as a part of the Microsoft 365 software, facilitates an online interface for collaborative activities (Tan et. al., 2022).…”
Section: Introductionmentioning
confidence: 99%